Preparing the patient for surgery to improve outcomes. Issue 2 (June 2016) - Levett, Denny Z.H.; Edwards, Mark; Grocott, Mike; Mythen, Monty
Abstract : The time between contemplation of surgery and the procedure offers a window of opportunity to optimize patients' nutritional, functional and psychological state prior to surgery. Traditionally, preoperative pathways have focused on the underlying disease process and 'fitness for surgery' with physical pre-assessment and risk counselling late in the pathway when little time is available to intervene. With an increasingly elderly and co-morbid surgical population, early physiological assessment and multidisciplinary collaborative decision-making is increasingly important. Multimodal prehabilitation programmes may improve surgical outcome, facilitating rapid recovery from surgery and limiting post-operative functional dependence. Patient education and engagement is important if compliance with behavioural change is to be achieved and maintained. To date, there has been evidence supporting preoperative exercise training, smoking cessation, reduction in alcohol intake, anaemia management and psychosocial support. Further research is needed to identify the most effective elements of these complex preoperative interventions, as well as their optimum timing and duration.